Music in the Protagonist’s World, the Protagonist in the World of Music: Liudmila Ulitskaya: The Big Green Tent - Szabó, Tünde (Literatūra, 2021)
The article examines the musical component in L. Ulitskaya’s novel The Big Green Tent. The first part provides an overview of those musical elements – realities, prototypes of individual characters and pretexts with musical themes, with the help of which an autonomous world and the image of one of the main characters of the work are created. The second part analyzes a fragment of the novel, which mixes musical and literary principles of text organization and creates a multidimensional connection with S. Rakhmaninoff’s Symphonic Dances. The analysis shows that the musical component in Ulitskaya’s novel performs a double function – constructing one of the plot lines and musicalizing certain fragments of the text.